Pendidikan Sebagai Upaya Pemerdekaan Manusia - Paulinus Kanisius Ndoa; Stefanus Hulu (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2023)
Today, the world of education is experiencing a shift from its true values. The education system used places too much emphasis on intellectual aspects, textual values, and charitable morality. However, they pay less attention to aspects of personal character formation, value education, and sensitivity and social responsibility. This situation should not be allowed to continue. Now is the time for stakeholders who are involved in organizing education to return education to the